Use of Glyphosate and Herbicide Alternatives for Weed Control in Florida Landscape Planting Beds - Chris Marble; Joe Neal; Andy Senesac (EDIS)
This new 10-page article is written for landscape professionals and those maintaining landscape areas to guide them in selecting alternatives to glyphosate (the active ingredient in RoundUp®) for postemergence weed control in Florida. Information is also included on preemergence herbicides and integrated weed management (use of chemical and non-chemical controls), which should be the basis of a weed management program. Written by Chris Marble, Joe Neal, and Andy Senesac, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep580